2022
DOI: 10.1186/s12889-022-14079-8
|View full text |Cite
|
Sign up to set email alerts
|

Does financial literacy influence preventive health check-up behavior in Japan? a cross-sectional study

Abstract: Background General health check-ups are an important element of healthcare, as they are designed to detect diseases, thereby reducing morbidity and mortality. Recent studies have found that financial literacy promotes preventive healthcare usage and reduces risky health behaviors such as smoking, lack of exercise, and gambling. Based on this evidence, we hypothesize that financial literacy, as a rational decision-making tool, is positively associated with health check-up behavior in Japan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
3
1
1
Order By: Relevance
“…This study found that 53.4% of participants underwent health checkups in the past 3 years. This figure is relatively higher than that reported by Ohnishi et al and Lal et al [14][15] , who studied the working-age population in Japan and found health checkup rates in the past year ranging from 31.8% to 43.9%. The prevalence of health checkups studied in the current research was based on 3-year data according to Thailand's health checkup guidelines 4 ; meanwhile, the Japanese study collected 1-year data.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…This study found that 53.4% of participants underwent health checkups in the past 3 years. This figure is relatively higher than that reported by Ohnishi et al and Lal et al [14][15] , who studied the working-age population in Japan and found health checkup rates in the past year ranging from 31.8% to 43.9%. The prevalence of health checkups studied in the current research was based on 3-year data according to Thailand's health checkup guidelines 4 ; meanwhile, the Japanese study collected 1-year data.…”
Section: Discussioncontrasting
confidence: 58%
“…The population in the current study received services at Vajira Hospital, located in urban areas, where higher rates of health checkups are typically observed compared with those in rural populations 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Our main explanatory variable, financial literacy, was measured using three questions in (Appendix B) following some existing literature [10,19,[27][28][29][30][31][32]. We assigned one point for each correct answer and zero points for each incorrect answer.…”
Section: Methodsmentioning
confidence: 99%
“…Es importante destacar que, de acuerdo con estudios de Cardona-Montoya et al ( 2022), la educación financiera es un catalizador del estado emocional, reduciendo la posibilidad de sufrir estrés, ansiedad y depresión, a lo que Lal et al (2022) agregan que está relacionada con la salud física.…”
Section: Educación Financiera Como Habilidad Del Siglo XXIunclassified